From Exile to Belonging: The [re]construction of Identity in the Context of Forced Migration - Massoud Sharifi Ahmadipour; Teresa Sordé-Martí (RIMCIS)
Focusing on Syrian and Afghan refugees and asylum seekers in Spain and Greece, this study employs social identity theory and intergroup contact theory to examine the process of identity construction. Drawing from thirty-five semi-structured interviews, the study highlights how the positive distinctiveness of their homeland and community significantly shapes their sense of self-worth, despite having fled due to persecution. The study finds that Afghan and Syrian refugees alike demonstrate a close attachment to their natural heritage, while also assigning particular importance to the historical and cultural legacies of their native lands. This sense of homeland identity interlaces with a multifaceted self-representation, mirroring the intricate ties between the host and homeland. Three identity discourse patterns appear: persecuted identity, identity conciliation, and critical consciousness. The refugees' dual perception of their homeland, as both a failed and desired land, influences their perceived self-worth in interpersonal interactions, as well as their sense of integration within the host society.